2007
DOI: 10.1002/hep.21855
|View full text |Cite
|
Sign up to set email alerts
|

N-glycomic changes in hepatocellular carcinoma patients with liver cirrhosis induced by hepatitis B virus

Abstract: We evaluated the use of blood serum N-glycan fingerprinting as a tool for the diagnosis of hepatocellular carcinoma (HCC) in patients with cirrhosis induced by hepatitis B virus (HBV). A group of 450 HBV-infected patients with liver fibrosis or cirrhosis with or without HCC were studied. HCC was diagnosed by ␣-fetoprotein (AFP) analysis, ultrasonography, and/or computed tomography and was studied histologically. N-glycan profiles of serum proteins were determined with DNA sequencer-based carbohydrate analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
153
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 156 publications
(175 citation statements)
references
References 36 publications
19
153
3
Order By: Relevance
“…5). In this same narrowed patient setting, the diagnostic accuracy for the GlycoHCCtest was 62% (9%), with a sensitivity and specificity of 50% and 70%, respectively, at the published cutoff of Ϫ0.34 (12 ).…”
Section: Markermentioning
confidence: 83%
See 1 more Smart Citation
“…5). In this same narrowed patient setting, the diagnostic accuracy for the GlycoHCCtest was 62% (9%), with a sensitivity and specificity of 50% and 70%, respectively, at the published cutoff of Ϫ0.34 (12 ).…”
Section: Markermentioning
confidence: 83%
“…The GlycoHCCTest enables the differentiation of HBVinfected patients with HCC from cirrhosis patients, with an overall sensitivity (57%) and specificity (88%) similar to that of serum AFP (12 ). However, serum glycoproteins represent a large group of glycoproteins synthesized by both the liver and plasma cells.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Whole cell ELISA showed that the recombinant wild-type EGFR mAb exhibited dose-dependent binding to A431 cells, comparable to Erbitux (Figure 1). N-glycan analysis revealed 7 dominant N-glycan structures (peaks) in the N-glycan profile, with only peak 2 and peak 7 containing bisecting GlcNAc residues [10,11] . Thus, the glycanmodified EGFR mAb with elevated abundances of peak 2 and peak 7 (bisec-EGFR mAb) was selected for further study.…”
Section: (Bisec-)egfr Mab Expression and N-glycan Analysismentioning
confidence: 99%
“…Following coexpression of GnTIII and wild type EGFR mAb in this cell line, we characterized the N-glycan profile of the GnTIII-modified EGFR mAb (bisec-EGFR mAb) using DNA sequencerassisted-fluorophore-assisted capillary electrophoresis (DSA-FACE) [10,11] and quantified the α-Gal content. The effects of the EGFR mAb on cell growth, ADCC and FcγR binding capacity were investigated in vitro to assess the functions of the bisec-EGFR mAb.…”
Section: Introductionmentioning
confidence: 99%
“…Vanhooren et al Serum N-glycan biomarker 13 using different N-glycans from GlycoAgeTest (Callewaert et al, 2004;Liu et al, 2007). As the changes in N-glycans are a consequence of genetic and environmental influences and physiologic responses, the GlycoAgeTest marker has a significant diagnostic potential.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%